Process development unit experimental studies of a split‐flow modification for the post‐combustion CO2 capture process. Issue 2 (30th January 2017) - Stec, M.; Tatarczuk, A.; Więcław‐Solny, L.; Krótki, A.; Spietz, T.; Wilk, A.
Abstract: A process development unit (PDU) for amine‐based post‐combustion carbon capture located at Clean Coal Technologies Centre in Zabrze, Poland, was used to validate split‐stream configuration. A PDU having capacity up to 100 m 3 n /h was designed to test the amine scrubbing carbon capture process from flue gases or mixtures of technical gases. Flexible process flow sheet of the unit allowed investigation of the split flow process. The split‐flow flowsheet modification was compared with a standard system for chemical absorption‐based CO2 capture. The tests were conducted using well‐accepted baseline solvent: 30 wt% aqueous monoethanolamine solution. The flow sheet modification resulted in a decrease of reboiler heat duty by ~1.6% and an increase in CO2 recovery by ~1.2 p.p. Split‐flow process modification was examined together with standard process flow sheet, and vast number of process parameters recorded during the trials have been presented. The explanation of beneficial effects of split‐flow designs have been shown together with detailed analysis of experimental trials carried out using PDU for amine‐based post‐combustion carbon capture. This paper is also a valuable source of experimental data useful during validation of models. Copyright © 2017 Curtin University of Technology and John Wiley & Sons, Ltd.